REVIEW OF MONOGRAPGH: FARKHUTDINOV I.Z. AMERICAN DOCTRINE OF PREVENTIVE STRIKES FROM MONROE TO TRUMP: INTERNATIONAL LEGAL ASPECTS. MOSCOW. 2017. 338 P. (IN RUSS.) - V. V. Aleshin; R. A. Kalamkaryan; V. N. Kulebyakin (Московский журнал международного права, 2018)
The review of the monograph highlights the academic and practical significance of a conceptual holistic analysis of the subject of study as a phenomenon of modern international relations. The monograph considers the process of development and implementation of the American doctrine of pre-emptive strike from Monroe to Trump from the point of view of modern international law. By all objective indicators the presented academic work by substance qualitatively differs from the existing array of related subject works of Russian specialists in international law. Moreover, none of the related academic works is equal in law or in fact to the considered monograph.. Relevant to the law of international security this monograph meets the objective academic criteria of comprehensiveness of research of the stated issues. Substantively the monograph fits the format of the international legal positioning by the Russian Federation as being a state whose foreign policy is designated to ensure good faith implementation by all States members of the world community of their international obligations (Article 2 (2) of the UN Charter). Consisting of eight chapters, the monograph represents a complete scientific study of the subject of the law of international security conducted at a high level of the modern science of jurisprudence. In the parameters of its scientific importance and practical applicability in the framework of a coherent foreign policy of Russia on the rule of law in the system of international relations, this monograph establishes appropriate legal methods in terms of building of a new world order. The work shows the process of formation and realization of American doctrine of preventive strikes from Monroe to Trump from the point of view of modern international law, its essence and significance.